Methylation and acetylation enhanced the antidiabetic activity of some selected flavonoids: In vitro, molecular modelling and structure activity relationship based study - Ahmed, Qamar Uddin; Sarian, Murni Nazira; Mat So'ad, Siti Zaiton; Latip, Jalifah; Arief Ichwan, Solachuddin Jauhari; Hussein, Nurlaili Najmie; Bakhtiar, M. Taher; Alhassan, Alhassan Muhammad; Hamidon, Hanisuhana; Fakurazi, Sharida (MDPI, 2018)
Flavonoids have been reported to exert antihyperglycemic effects and have potential to enhance the current therapy options against type 2 diabetes mellitus. However, the structure activity relationships (SAR) studies of flavonoids against this disease have not been thoroughly comprehended. Hence, in the present study, 14 structurally related flavonoids viz. wogonin, techtochrysin, norwogonin, isoscutellarein, hypolaetin, kaempferol, quercetin, methyl ether of wogonin, acetate of wogonin, acetate of norwogonin, 8-hydroxy-7-methoxyflavone, chrysin, (+)-catechin and (-)-epicatechin were taken into account for in vitro antidiabetic evaluation. Cell viability of RIN-5F pancreatic cells and 3T3-L1 pre-adipocyte cells was initially tested, then an insulin secretion assay of RIN-5F as well as adipogenesis and glucose uptake measurements of adipocyte were investigated. Subsequently, protein expressions study through adipokines measurement (leptin, adiponectin, TNF-α, RBP-4) via enzyme-linked immunosorbent assay (ELISA) kit, Western blotting analysis against GLUT4 and C/EBP-α as well as molecular docking against GLUT1 were analyzed. The results from cell culture antidiabetic assays (insulin secretion, adipogenesis, and glucose uptake), protein expressions and molecular docking pointed that the methoxy group at position C-8 is responsible for antidiabetic property of selected flavonoids via glucose uptake mechanism indicated by up regulation of GLUT4 and C/EBP-α expressions. The mechanism could be enhanced by the addition of an acetate group at C-5 and C-7 of the flavone skeleton.